ANALYSIS OF PAYMENT FRAUD CRIMINAL ACTIONS IN USED CAR BUYING AND SALE TRANSACTIONS THROUGH FACEBOOK MARKETPLACE IN MEDAN CITY - Difta Hadi; Tri Reni Novita; Muhammad Ridwan Lubis; Herlina Hanum Harahap (Jurnal Ilmiah METADATA, 2026)
This study aims to analyze the modus operandi, the application of criminal law provisions, as well as obstacles and efforts to overcome the crime of payment fraud in used car buying and selling transactions through Facebook Marketplace in Medan City. This study uses an empirical legal method with a qualitative approach supported by a normative juridical approach. Data were obtained through interviews with investigators from Unit V Cyber ​​Ditreskrimsus Polda Sumatera Utara and victims, as well as through documentation and observation studies. The results of the study indicate that the perpetrators used fake accounts and identities, manipulated photos and descriptions of vehicles, requested down payments or payments in full before the vehicles were inspected, utilized escrow accounts, and falsified vehicle ownership or guarantee status. The application of the law is based on Article 378 of the Criminal Code (KUHP) which is linked (juncto) with Article 28 paragraph (1) of the Electronic Information and Transactions Law. The main obstacles faced include differences in interpretation between fraud and default, difficulties in tracking the perpetrator's identity, limited access to cross-platform data, the complexity of electronic evidence, low digital literacy in the community, and the reluctance of victims to report. Mitigation efforts are carried out through education, cyber patrols, strengthening digital forensic capacity, collaboration with platform providers, law enforcement, and victim assistance. This study concludes that addressing online fraud requires cross-agency coordination, increased investigator capacity, and public literacy to ensure legal protection and certainty for victims are implemented effectively, consistently, and responsive to developments in information technology.